Floral Scents and Fruit Aromas: Functions, Compositions, Biosynthesis, and Regulation - Mostafa, Salma; Wang, Yun; Zeng, Wen; Jin, Biao (Frontiers in Plant Science, 2022)
Floral scents and fruit aromas are crucial volatile organic compounds (VOCs) in plants. They are used in defense mechanisms, along with mechanisms to attract pollinators and seed dispersers. In addition, they are economically important for the quality of crops, as well as quality in the perfume, cosmetics, food, drink, and pharmaceutical industries. Floral scents and fruit aromas share many volatile organic compounds in flowers and fruits. Volatile compounds are classified as terpenoids, phenylpropanoids/benzenoids, fatty acid derivatives, and amino acid derivatives. Many genes and transcription factors regulating the synthesis of volatiles have been discovered. In this review, we summarize recent progress in volatile function, composition, biosynthetic pathway, and metabolism regulation. We also discuss unresolved issues and research perspectives, providing insight into improvements and applications of plant VOCs.